Uso del ensilaje de bagazo de caña de azúcar (Saccharum officinarum) para mejorar la producción lechera de Bovinos en el trópico Ecuatoriano - Sánchez Tobar, Génesis Mishell (2021)
The feeding of cattle in the tropics depends almost exclusively on pastures, and these show an irregular supply during certain times of the year. This work was carried out with the objective of analyzing the use of sugarcane bagasse silage to improve the dairy production of cattle in the Ecuadorian tropics. The Qualitative and Exploratory method was used, in a database with information obtained from dspace of the universities, indexed journals, national and international scientific articles, experimental works, documents and reports, virtual library. The use of silage from sugarcane bagasse is a feeding alternative as a supplement for cattle in times of low pasture yield. bromatological analyzes of sugarcane bagasse show that they contain: protein 3.0%, ash 7.3%, crude fiber 38.02%, dry matter 86.26, fat, 1.2%, carbohydrates 25.8. According to what was investigated, the milk production presented a significant favorable difference with the use of simplified bagasse; they obtained 6.81 kg of yield milk against 4.96 kg in the control group.